Mise en scène des corps et interfaces gestuelles dans une exposition sur le jeu vidéo - Marion Coville (Tracés, 2015)
This paper follows from a PhD research about an exhibition curated by La Cité des sciences on video games, Jeu Vidéo, L’Expo. An exhibit, Communautés Créatives (CC), is designed for consulting informational content about video games. Kinect, a gestural and touchless interface is used to select content. Imagined to play video games between friends or family on an Xbox360 console, CC designers repurpose Kinect from its original use. This article explores how visitors domesticate CC. They usually don’t pay attention to CC’s contents but try to understand how it works, sometimes turning this action into a fun activity. These activities take place in an exhibition where visitors’ bodies are essential components of the museography. The article studies the implications of the body visibility and involvement, in a public context of representation in a museum, for visitors’ actions. Visitors’ action is confined by a doubt. It comes from the exhibition’s general context, from visitors watching other visitors in action, and from the lack of informations about this installation’s uses.